Fibrilace síní a městnavé srdeční selhání - Roy, Denis; Talajic, Mario; Dubuc, Marc; Thibault, Bernard; Guerra, Peter; Macle, Laurent; Khairy, Paul (Current opinion in cardiology (České vyd.), 2009)
The present review will examine the prognostic importance of atrial fibrillation and heart failure, explore the different therapeutic options for treating atrial fibrillation and present the results of the Atrial Fibrillation and Congestive Heart Failure (AF-CHF) trial. RECENT FINDINGS: The Atrial Fibrillation and Congestive Heart Failure trial was a randomized trial involving patients with both atrial fibrillation and heart failure. The trial was designed to compare the maintenance of sinus rhythm with the control of ventricular rate in patients with left ventricular dysfunction, heart failure and a history of atrial fibrillation. There was no significant difference in the rate of death from cardiovascular causes in the rhythm-control group as compared with the rate-control strategy. In addition, there was no significant difference in any of the secondary outcomes including death from any cause, worsening heart failure or stroke. The rate-control strategy eliminated the need for repeated cardioversion and reduced rates of hospitalization. SUMMARY: The results of the Atrial Fibrillation and Congestive Heart Failure trial indicate that a routine strategy of rhythm control does not reduce rate of death and suggest that rate control should be considered a primary approach for patients with atrial fibrillation and heart failure.
Keywords: Comorbidity; antiarytmika; digoxin; Adrenergic beta-Antagonists; Cardiomyopathies; beta blokátory; Humans; kardiomyopatie; lidé; Anti-Arrhythmia Agents; fibrilace síní; Anticoagulants; Catheter Ablation; tachykardie; srdeční selhání; Tachycardia; Randomized Controlled Trials as Topic; antikoagulancia; komorbidita; randomizované kontrolované studie jako téma; Digoxin; katetrizační ablace; srdeční frekvence; Atrial Fibrillation; Heart Failure; Heart Rate